Molecular detection and characterization of Anaplasma spp. in sheep and cattle from Xinjiang, northwest China - Yang, Jifei (Parasit Vectors, 2015)
BACKGROUND: Anaplasmosis is caused by obligate intracellular bacteria in the genus Anaplasma. These bacterial pathogens are transmitted by ticks and impact both human and animal health. This study was conducted to determine the prevalence and molecular characterization of Anaplasma spp. in ruminants sampled in Xinjiang, northwest China. METHODS: A survey was performed in August 2012 in rural areas of six counties in Xinjiang province. A total of 250 blood samples from ruminants were collected and tested for the presence of Anaplasma spp. by PCR. Positive samples were genetically characterized based on the 16S rRNA and msp4 genes. RESULTS: The results showed a high prevalence of Anaplasma spp. in ruminants, with at least three different Anaplasma species detected (A. phagocytophilum, A. bovis and A. ovis). The mean prevalence of single infection with each species was 17.6% (A. phagocytophilum), 4.8% (A. bovis) and 40.5% (A. ovis). Coinfection occurred in 20 (8.0%) animals. Phylogenetic analysis of the 16S rRNA gene of A. bovis and A. phagocytophilum revealed a higher degree of genetic diversity for the latter. The results for A. ovis showed genotypic variation among geographic regions in China. In addition, a closely related isolate to the canine pathogen A. platys was identified in ruminants. CONCLUSIONS: This survey revealed a high prevalence of Anaplasma sp. infections in sheep and cattle in the northwestern border regions of China, indicating the potential risk of transboundary disease.